Heterogeneity of demands for nature’s contributions to people and nature’s values by farmers: insights from the Kilimanjaro social-ecological system - John Sanya; Milena Gross; Tuyeni H Mwampamba; Jasmine Pearson; Jennifer K Sesabo; Maraja Riechers; Neema R Kinabo; Viviane Krail; Berta Martín-López (Ecology and Society, 2025)
Farmers are not a homogeneous social actor group, particularly regarding their demands for nature’s contributions to people (NCP) and how they value nature. Overlooking internal heterogeneity prevents them from implementing inclusive conservation that aligns with their needs and interests. We aimed to explore the internal heterogeneity of the NCP demands and values of nature expressed by farmers, considering their socio-demographic characteristics, pro-environmental behavior, and geographical context. Additionally, we aimed to understand how perceptions of NCP supply trends over the last decade affect demands for NCP. Using a socio-cultural valuation approach, we conducted face-to-face surveys with 364 farmers residing in 14 villages located on the southern slope of Mount Kilimanjaro, Tanzania. Based on descriptive and redundancy analyses (RDAs), we found that farmers primarily preferred material and regulating NCP: food, feed, and regulation of freshwater quality, whose supply is perceived as decreasing, i.e., “critical” NCP. Regarding values of nature, we found the highest farmers’ share of agreement for statements representing intrinsic value (97.1% of respondents who agreed or strongly agreed), relational values (94.8%), and instrumental values (94.1%), although the pattern for individual value statements varied slightly. The RDA findings indicated that altitudinal and longitudinal gradients, the place of birth of both respondents and their parents, and engagement in conservation activities strongly influenced the distinctive demands for NCP and nature’s values. Values of nature were also influenced by age, education, and membership in any association. Moreover, we found seven bundles of NCP demands that represent distinct ways in which farmers use and appreciate nature. These findings deepen the understanding of the interlinkages between NCP demands, perceived NCP supply trends, and the valuation of nature according to the internal heterogeneity of farmers, which is essential to elaborate evidence-based strategies for nature conservation that align with their interests and needs.